Small and Medium Enterprise in the Regional Environment Conditions - Mandysová, Ivana (Mendelova univerzita v Brně, 2016)
Entrepreneurship has become an important issue. There are a heterogeneous group of units working in various fields and sectors of economy. The business landscape consists of many small and medium sized enterprises operating in a manufacturing sector, service and trade, like machine workshops, handcrafts makers, computer software enterprises. They are classified by the number of employees or total turnover level. These enterprises have all been started by an entrepreneur who has identified a business idea and changed that into a venture. In some geographical regions more enterprises are started than in other geographical locations. These enterprises are often started in the same field of industry which has led to theories that the environment supports and stimulates entrepreneurship. Studies about regional conditions have often been conducted and they have studied ties and contacts in the regional environment.
Malý a střední podnik v podmínkách regionálního prostředí
Keywords: region; regional environment; entrepreneurship; small and medium sized enterprise; region; regionální prostředí; podnikání; malý a střední podnik